A technical survey of Lucky Madlo Sibiya’s (1942 – 1999) materials and techniques employed in his carved and painted wood panel artworks - Loubser, Maggi (University of Pretoria, 2021)
Mini Dissertation (MSocSci)--University of Pretoria, 2020.